POSSIBLE CORRELATES OF POSTTRAUMATIC GROWTH AMONG PATIENTS WITH TYPE II DIABETES - Emre ŞENOL-DURAK; Mithat DURAK; Özlem BOZO (Nesne Psikoloji Dergisi, 2020)
Diabetes, a chronic illness, affects individuals' lives dramatically. The present study aims to evaluate the role of social support, self-efficacy, diabetes-related variables (perceived threat, treatment type, perceived prognosis and time passed since diagnosis), and cognitive processing on Posttraumatic Growth (PTG) among outpatients with diabetes with a history of inpatient treatment. Within a theoretical framework of the model of Schaefer and Moos (1998), the roles of social support, self-efficacy, diabetes-related variables, and cognitive processing have been examined by employing structural equation modeling in a sample of outpatients with diabetes having a history of at least one inpatient treatment (N = 275). Diabetes-related factors mediated the relationship between social support and PTG. Also, cognitive processing mediated the relationship between self-efficacy and PTG. Enhancing patients' self-efficacy and facilitating their social support network should be taken into consideration when designing psychosocial intervention programs for patients with diabetes because such programs require high self-control over one’s health.